Subcarrier‐pair based joint resource allocation for secure cooperative OFDM system with multiple untrusted AF relays. Issue 9 (19th April 2022) - Jin, Yifeng; Li, Xunan; Lv, Guocheng; Zhao, Meihui; Jin, Ye
Abstract: In this paper, a cooperative orthogonal frequency division multiplexing system with multiple untrusted amplify‐and‐forward relays is considered. Since there exists no direct link between source and user because of the shadowing effect, a positive system secrecy rate cannot be obtained. Addressing this issue, a cooperative user‐aided jamming technique to improve the secrecy performance is employed. With the aim of maximising the system secrecy rate, a joint resource allocation problem of power allocation, relay assignment and subcarrier pairing is formulated. By using the signal‐to‐noise ratio based approach and the Lagrange dual method, this nonconvex problem is solved efficiently. To reduce the calculation complexity, a suboptimal algorithm, which decouples the power allocation with the relay assignment and subcarrier pairing is further proposed. Numerical results are presented to demonstrate the advantage of the two proposed algorithms and the impact of relays' location and number of subcarriers on the secrecy performance. Moreover, it is shown that the secrecy performance of the proposed scheme is decreased with respect to the number of untrusted relays.